Báo cáo Giải trình, tiếp thu, chỉnh lý dự thảo Nghị quyết Kỳ họp thứ 6, Quốc hội khóa XV - Ủy ban Thường vụ Quốc hội (2023)
Toàn văn Báo cáo Giải trình, tiếp thu, chỉnh lý dự thảo Nghị quyết Kỳ họp thứ 6, Quốc hội khóa XV.